Effect of Content and Particle Size of Used Beverage Carton Pieces on the Properties of HDPE Composites - Kuzmin, Anton Michailovich; Ayrilmis, Nadir; Ozdemir, Ferhat; Kanat, Gurdal (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2023)
This study investigated the tensile properties and thermal behavior of virgin and hot press molded HDPE composites filled with different particle size and content of used beverage cartons which were the Tetra Pak (R) cartons. The mechanical properties of the composites were positively influenced by particle size of the used beverage carton, such that the smallest particle size gave the highest tensile strength and tensile modulus. The tensile strength of the specimens decreased with increasing filler content (40 to 70 wt%), while the tensile modulus rose. Furthermore, the filler size and its content affected the thermal behavior of the specimens. Calorimetry analysis of composite specimens showed that melting temperature and enthalpy values of virgin HDPE and recycled-HDPE decreased with increasing Tetra Pak (R) content. In all composite groups produced by adding Tetra Pak (R), the degree of crystallinity decreased as a function of Tetra Pak (R) addition compared to the pure HDPE. Increasing particle size adversely affected the crystallization degree, which decreased with increasing particle size while the HDPE maintained its crystalline form. As for the recycled-HDPE composites, the degree of crystallization was reduced by increasing the Tetra Pak (R) content, but this was still noticeably higher than that of the HDPE.
Keywords: Tetra Pak; Filler; Thermal behavior; Strength; Particle size; Filler content; MECHANICAL-PROPERTIES; THERMAL-PROPERTIES; CARDBOARD PANELS; POLYETHYLENE; WASTE; Materials Science